Using touchscreen tablets to support social connections and reduce responsive behaviours among people with dementia in care settings: A scoping review. (April 2021) - Hung, Lillian; Chow, Bryan; Shadarevian, John; O'Neill, Ryan; Berndt, Annette; Wallsworth, Christine; Horne, Neil; Gregorio, Mario; Mann, Jim; Son, Cathy; Chaudhury, Habib
The use of touchscreen tablets, such as the iPad, offers potential to support the person with dementia staying in a care setting, ranging from a long-term care home to an adult day programme. Although electronic devices are used among people with dementia, a comprehensive review of studies focusing on their impact and how they may be used effectively in care settings is lacking. We conducted a scoping review to summarize existing knowledge about the impact of touchscreen tablets in supporting social connections and reducing responsive behaviours of people with dementia in care settings. Our research team consists of patient partners and family partners, physicians, nurses, a medical student and an academic professor. A total of 17 articles were included in the review. Our analysis identified three ways in which touchscreen tablets support dementia care: (1) increased the person's engagement, (2) decreased responsive behaviours and (3) positive effect on enjoyment/quality of life for people with dementia. Lessons learned and barriers to the use of touchscreen tablets in the care of people with dementia are described. Overall, only a few studies delineated strategies that helped to overcome barriers to technology adoption in care settings. Knowledge translation studies are needed to identify effective processes and practical tips to overcome barriers and realize the potential of assistive technology in dementia care.